A High Throughput Three-step Ultra-performance Liquid Chromatography Tandem Mass Spectrometry Method to Study Metabolites of Atractylenolide-III. Issue 2 (29th November 2018) - Jiang, Zhihui; Peng, Chunyan; Huang, Wenping; Wu, Bei; Zhang, Dan; Ouyang, Hui; Feng, Yulin; Yang, Shilin
Abstract: Atractylodes macrocephala Koidz (AMK) is a traditional Chinese medicine widely used in the treatment of various diseases, especially spleen deficiency. As the principle active constituents of AMK, however, the metabolites of Atractylenolide-III (A-lactone-III) have not been identified in rats yet. In this study, a three-step high throughput method based on UHPLC–Q-TOF–MS-MS was developed to profile and characterize the metabolites of A-lactone-III in rat feces, urine and plasma. The initial step was a full-scan that utilized a multiple mass defect filter (MMDF) combined with dynamic background subtraction (DBS). PeakView ® 1.2 and Metabolitepilot™1.5 software was then used to obtain data and seek possible metabolites. Finally, MS-MS spectra of the parent drug and possible metabolites were compared by the fragment ion peaks and retention times, which enabled metabolites to be identified. As a result, 53 metabolites were characterized in rats in vivo. The metabolic pathways of A-lactone-III were identified as including methylation, oxidation, hydroxylation, dihydroxylation, hydrogenation, glycosylation, sulfonation, and glucuronide, cysteine and N -acetylcysteine conjugation.